Geranylgeraniol Reverses the Toxicity Induced by Clinical Doses of Zoledronic Acid on Gingival Epithelial Cells and Gingival Fibroblasts - Koneski, Filip; Tipton, David; Babu, Jegdish; Popovic-Monevska, Danica; Popovski, Vladimir; Benedetti, Alberto; Dvojakovska-Bozovic, Suzana; Iliev, Aleksandar; Panchevski, Goran; Kirkov, Antonio; Grchev, Aleksandar; Stamatoski, Aleksandar; et al. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Medication-related osteonecrosis of the jaw (MRONJ) is of considerable concern among clinicians and researchers, with no clear pathology mechanism, preventive, or treatment protocols. AIM: This study aimed to assess the effects of geranylgeraniol (GGOH) on the toxicity induced by clinical doses of zoledronic acid (ZOL) on gingival epithelial cells and gingival fibroblasts in vitro. METHODS: Human gingival fibroblasts and gingival epithelial cells were treated with 5, 25, or 50 μM ZOL ± 50 μM GGOH for 3 days. Viability of the cells was determined using the 3-[4, 5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide assay. Calculation of percentage of the control group, analysis of variance and Tukey post-hoc comparisons were performed to test the significance between groups, which was set at p = 0.05. Cell morphology was evaluated using light microscopy. RESULTS: ZOL significantly reduced the viability of both epithelial cells and fibroblasts at all concentrations (p < 0.05), with the exception of fibroblasts at concentration of 5 μM (p = 0.44). GGOH had positive effects on the viability of the cells treated with ZOL at all concentrations. However, statistically significant improvement was obtained only in epithelial cells at 5 and 25 μM ZOL. The cell morphology of both types of cells was improved after addition of GGOH. CONCLUSION: GGOH reverses the toxic effects of clinical doses of ZOL on gingival epithelial cells and has slightly positive, but not significant effects on gingival fibroblasts. This study suggests that GGOH may be effective in the prevention and treatment of MRONJ.